2005
DOI: 10.1108/02632770510578502
|View full text |Cite
|
Sign up to set email alerts
|

Network service organisation: a multiple pilot study

Abstract: PurposeCentralised workplace and decentralised facilities management organisations combine several interacting functions. Different levels of a network service organisation are presented. The interacting functions are divided into three organisational levels: strategic clients, network integrators, and functional service units. The research paper demonstrates proposals, data collection plans, and relevant lines of questioning for future case studies and network analysis on the basis of the connections discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Previous studies on supply chains and networks in the context of facility services have been mostly interested in outsourcing decisions (Ventovuori, 2007;Carr, 2011;Plane and Green, 2012) or characteristics, performance consequences and success factors of individual buyer -supplier relations (Lehtonen, 2006;Heimbürger and Dietrich, 2012). However, given the decisions to outsource, only a few studies have examined how the inter-organisational entities are designed and managed (Salonen, 2004;Tuomela and Salonen, 2005;Van Mossel and Van der Valk, F 32,11/12 2008;Blomé, 2010). Lacking prior research on supply network design in the context of FM the study aims to answer the following research question: RQ1.…”
Section: Supply Networkmentioning
confidence: 99%
“…Previous studies on supply chains and networks in the context of facility services have been mostly interested in outsourcing decisions (Ventovuori, 2007;Carr, 2011;Plane and Green, 2012) or characteristics, performance consequences and success factors of individual buyer -supplier relations (Lehtonen, 2006;Heimbürger and Dietrich, 2012). However, given the decisions to outsource, only a few studies have examined how the inter-organisational entities are designed and managed (Salonen, 2004;Tuomela and Salonen, 2005;Van Mossel and Van der Valk, F 32,11/12 2008;Blomé, 2010). Lacking prior research on supply network design in the context of FM the study aims to answer the following research question: RQ1.…”
Section: Supply Networkmentioning
confidence: 99%
“…For FM, the network organisation is composed of multiple clients and service providers supporting core business functions ( Tuomela and Salonen, 2005 ). The network alliance should not be affected by location, position or the service functions ( Tuomela and Salonen, 2005 ).…”
Section: The Strategic Importance Of the Afm Functionmentioning
confidence: 99%
“…The network alliance should not be affected by location, position or the service functions ( Tuomela and Salonen, 2005 ). Changes in the past decade in AFM have in part been caused by the role of the government, deregulation, and also the increased use of network activities.…”
Section: The Strategic Importance Of the Afm Functionmentioning
confidence: 99%
“…In the beginning of the research, a literature review is suggested to be generated to identify potential research questions. To uncover the operability of designed research construct, a pilot study is conducted to redefine the plan of data collection [7] which is confirmatory focus. And the results have contributed to the final decisions related to target industry and case criteria.…”
Section: Methodsmentioning
confidence: 99%